Analisis Kesesuaian Materi Kuliah dengan Materi Praktikum Biologi Bidang Tumbuhan pada Prodi Pendidikan Biologi UIN Ar-Raniry - Elita Agustina (Universitas Islam Negeri Ar-Raniry, 2016)
The appropriacy of course content with practicum contents is an effort to reach an optimum instructional goal. The level of appropriacy also reflects the implementation of practicum in the laboratory. Nevertheless, there were still some weaknesses in the practicum implementation such as the practicum was not fully conducted under lecturerâ€™s guidance and direction; The practicum content was irrelevant with the course content; Evaluation and revision was rarely made to the course content and practicum content; the sequence of course content was not suitable with the sequence of practicum content. The aims of this study were to find out the level of appropriacy of course content with the content of biology practicum in the field of plant at biology education department. The methods used in this study were document analysis and descriptive method. The lesson plan of plant course content and also the content of practicum guidance in the field of plant were analyzed by the researcher. The result showed that 1) the level of appropriacy between the plant course content and the content of practicum was 50% and categorized as â€œappropriateâ€; 2) The other plant course content was considered â€œvery appropriateâ€ in terms of course content appropriacy with practicum content in the level of 50%. 3) The level of appropriacy between the sequences of course content with practicum content was 50% and categorized as â€œappropriateâ€. While another 50% was categorized as â€œvery appropriateâ€. It can be concluded that the level of appropriacy of course content with the content of biology practicum in the field of plant at biology education department of UIN Ar-Raniry was categorized by â€œvery appropriateâ€ and â€œappropriateâ€.